Protonation of Piezo1 Impairs Cell-Matrix Interactions of Pancreatic Stellate Cells - Kuntze, Anna; Goetsch, Ole; Fels, Benedikt; Najder, Karolina; Unger, Andreas; Wilhelmi, Marianne; Sargin, Sarah; Schimmelpfennig, Sandra; Neumann, Ilka; Schwab, Albrecht; Pethő, Zoltan (Frontiers in Physiology, 2020)
Pancreatic ductal adenocarcinoma (PDAC) is characterized by an acidic and fibrotic stroma. The extracellular matrix (ECM) causing the fibrosis is primarily formed by pancreatic stellate cells (PSCs). The effects of the altered biomechanics and pH landscape in the pathogenesis of PDAC, however, are poorly understood. Mechanotransduction in cells has been linked to the function of mechanosensitive ion channels such as Piezo1. Here, we tested whether this channel plays crucial roles in transducing mechanical signals in the acidic PDAC microenvironment. We performed immunofluorescence, Ca2+ influx and intracellular pH measurements in PSCs complemented by live-cell imaging migration experiments in order to assess the function of Piezo1 channels in PSCs. We evaluated whether Piezo1 responds to changes of extracellular and/or intracellular pH in the pathophysiological range (pH 6.6 and pH 6.9, respectively). We validated our results using Piezo1-transfected HEK-293 cells as a model system. Indeed, acidification of the intracellular space severely inhibits Piezo1-mediated Ca2+ influx in PSCs. In addition, stimulation of Piezo1 channels with its activator Yoda1 leads to enhanced migratory behavior of PSCs on a two-dimensional ECM as well as in a 3D setting. Furthermore, Yoda1-activated PSCs transmit more force to the surrounding ECM under physiological pH, as revealed by measuring the dislocation of microbeads embedded in the surrounding matrix. We found a similar effect on cytoskeletal level, as myosin light chain isoform 9 is highly phosphorylated after Piezo1 stimulation. Intriguingly, upon acidification, Yoda1 stimulation leads to the initiation of cell death and disruption of PSC spheroids. In summary, stimulating Piezo1 activates PSCs by inducing Ca2+ influx, and subsequently altering cytoskeletal architecture. This results in increased cellular motility and ECM traction, which can be useful for the cells to invade the surroundings and to detach from the tissue. However, in the presence of an acidic extracellular pH, even though net Ca2+ influx is reduced, Piezo1 activation leads to severe cell stress also limiting cellular viability. In conclusion, our results indicate a strong interdependence between environmental pH, the mechanical output of PSCs and stromal mechanics, which promotes early local invasion of PDAC cells.